Utilization of Engklek Game in Introducing the Concept of Numbers to Children Aged 4-5 Years - Nurlita, Nurlita; Miranda, Dian; Lukmanulhakim, Lukmanulhakim (International Journal of Learning and Instruction (IJLI), 2024)
This research aims to determine the use of the engklek game in introducing the concept of numbers in children aged 4-5 years at the Islamic Kindergarten in Pontianak. The method used in this research is a descriptive method with a qualitative research form. The subjects in this study were 10 children aged 4-5 years. Data collection tools using observation sheets, interview guidelines and documentation. The results of the research show that: (1) When children say numbers corresponding to the numbers 1-10, (2) Count the number of objects with the help of visual media in the form of pictures, (3) Connect number symbols in sequence where the child holds a hook and matches the numbers the in the game boxes, (4) Write the number symbols in sequence starting by writing the number 1 by following the example beside it.  Keywords: Engklek, Concept of Numbers, Number Symbols